2009
DOI: 10.1299/jfst.4.324
|View full text |Cite
|
Sign up to set email alerts
|

Instabiity and Encapsulation of a Compound Liquid Jet

Abstract: We analytically examine breakup phenomena of a compound liquid jet which consists of a gas or liquid core phase and a surrounding annular phase. Applying the long wave approximations to the basic equations and the boundary conditions for inviscid and incompressible fluids, simplified nonlinear equations are derived for large deformation of the jet. It is numerically shown for a doubly infinite jet that the core phase is periodically capsuled by the annular phase, whose profiles are largely affected by density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Moreover, a two-step finite difference scheme was used to study the effects of key parameters on breakup and drop formation. Other related studies are reported by Radev and Gospodinov [17], Yoshinaga and Maeda [24] and Yoshinaga and Yamamoto [25].…”
Section: Introductionsupporting
confidence: 57%
“…Moreover, a two-step finite difference scheme was used to study the effects of key parameters on breakup and drop formation. Other related studies are reported by Radev and Gospodinov [17], Yoshinaga and Maeda [24] and Yoshinaga and Yamamoto [25].…”
Section: Introductionsupporting
confidence: 57%
“…Resulting from this, we can determine the critical frequencies ω c which minimize t b for each parameters φ, η, Wb, Re, and σ. Such frequencies ω c are the most unstable input frequency in the sense of nonlinearity and we have shown they can well predict the natural formation periods of shells for the gas-cored jet (6) . This is expected to be still valid for the liquid-cored jet.…”
Section: Numerical Resultsmentioning
confidence: 76%
“…Later, Yoshinaga (6) showed that natural shell formation frequencies observed in the experiment for the gas-cored jet (3) are well predicted by using the most unstable frequencies of input disturbances which make the breakup time minimum. Although the above analysis was performed for an inviscid jet, it is not only preferable to consider the liquid viscosity for more precise analysis, but also the viscous effect is significantly important on the interface between the core and the annular phase for the liquid-cored jet.…”
Section: Introductionmentioning
confidence: 96%
“…Rou et al [17] have considered the three-dimensional linear instability of a viscous compound jet moving in an inviscid surrounding gas. Yoshinaga and Maeda [18] have simulated inviscid compound thread rupture and compared their results to the experimental work of Hertz and Hermanrud [5]. The inclusion of surfactants on the instability of compound threads has been considered by a number of authors (see, for example, Kwak and Pozrikidis [19]).…”
Section: Introductionmentioning
confidence: 99%